Sejarah Evolusi Generasi Internet - Saroji, Ahmad; Harmini, Triana; Taqiyuddin, Muhammad (Lani: Jurnal Kajian Ilmu Sejarah dan Budaya, 2021)
This study aims to trace the evolutionary history of the internet across generations, culminating in the fifth generation (5G). Over the last decade, internet technology has undergone rapid development. Each generation of internet technology—1G, 2G, 3 G, 4G, and 5G—comes with its own set of advantages and disadvantages. This article provides an overview of the features and specifications of these internet generations. It examines when Indonesia first adopted internet technology, including identifying the figure known as the "father of the internet" in Indonesia. The internet serves as a medium through which people access information from distant places they may never visit in person. It has become an essential communication tool, enabling connections at any time and from any location. The internet is also instrumental in simplifying human tasks. As inherently social beings, humans find it difficult to detach from social media, relying on the internet for activities such as browsing, chatting, and online learning, all of which have become integral to daily life.